Neutral Spanish in Specialized Discourse: Myth, Utopia, or Reality? - García Izquierdo, Isabel (Íkala, Revista de Lenguaje y Cultura, 2009)
This paper reflects on the possibility of achieving a neutral (international) Spanish, based on an analysis of some determining factors in the current configuration of the Spanish language. The limitations and drawbacks of a neutral Spanish notwithstanding, we defend its appropriateness, particularly in the field of scientific Spanish, as a tool to homogenize certain usages. This could enhance language cohesion in some contexts and, as a result, help Spanish to be viewed as a language of prestige. We also propose a conceptualization of neutral Spanish. We conclude by stating that neutral Spanish is not yet a reality but could become one if the different authorities involved in the standardization of specialized discourse were to agree on some basic criteria. Received: 07-05-09 /Accepted: 28-07-09 How to reference this article: García Izquierdo, I. (2009). El español neutro en los discursos de especialidad: ¿mito, utopía o realidad? Íkala. 14(3), pp.15-39.